Pericyte Contractile Responses to Endothelin-1 and Aβ Peptides: Assessment by Electrical Impedance Assay - Hibbs, Elliott; Love, Seth; Miners, J. Scott (Frontiers in Cellular Neuroscience, 2021)
Pericytes are vascular mural cells that contract and relax in response to vasoactive stimuli to regulate neurovascular coupling and cerebral blood flow. Pericytes are damaged and degenerate in Alzheimer’s disease (AD). We previously showed that the level of the regulatory vasoconstrictor, endothelin-1 (EDN1), is elevated in AD cerebral cortex and upregulated by amyloid-beta (Aβ). We have used electrical impedance analysis to monitor the contractile and proliferative response of cultured human fetal and adult brain-derived pericytes to EDN1 in real-time. EDN1 caused transient, dose-dependent contraction of fetal and adult brain pericytes that was mediated by EDN1 type A receptors and increased the subsequent proliferation of fetal but not adult cells. The contractile responses to EDN1 were weaker in the adult pericytes. The EDN1-mediated contractile response of fetal pericytes was unchanged after exposure to Aβ1–40 or Aβ1–42 (0.1–10 μM) for 1 h but both contraction and subsequent relaxation were significantly impaired upon exposure to Aβ for 24 h. These data suggest that chronic exposure to Aβ interferes with EDN1-mediated pericyte contractility, potentially contributing to neurovascular uncoupling and reduced cerebral blood flow in AD.